Predictable surprises the disasters you should have seen coming, and how to prevent them - Bazerman, Max H. (Boston Harvard Business School Press, 2004)
Even the best-run companies can get blindsided by disasters they should have anticipated. These predictable surprises range from financial scandals to operational disruptions, from organizational upheavals to product failures. In "Predictable Surprises", Max H. Bazerman and Michael D. Watkins show you how to minimize your risk by understanding and lowering the psychological, organizational, and political barriers preventing you from foreseeing calamity. They then describe the powerful tools - including incentives and formal coalitions - that business leaders can use to ferret out and fend off threats invisible to insiders. Failure see what's coming exposes your company to predictable surprises. Given the stakes involved, this book should count among every business leader's most trusted resources.
Leadership for the common good
Keywords: Emergency management